Time to stop irrigation on carrot seed production - Marquelli, Waldir A.; Carrijo, Osmar A.; Oliveira, Carlos A.S. (Pesquisa Agropecuaria Brasileira, 2014)
Three experiments were carried out under soil and climate conditions of Central Brazil to determine the adequate time to stop irrigations for carrot seed production. The treatments consisted of stopping irrigations at 60, 70, 80, 90, 100, 110, 120, 130 and 140 days after planting. Carrot seed production was found to be a quadratic function of time to stop irrigation. Large productivities were found when irrigation was stopped at 121 days after planting. Irrigation costs were optimized at this time. The weight of 1.000 seed and the crop cicle increased with the time to stop irrigations. Seed germination was not affected by the treatments.